Cognitive indicators of transition to preclinical and prodromal stages of Alzheimer's disease in Down syndrome. Issue 1 (13th September 2020) - Hartley, Sigan L.; Handen, Benjamin L.; Devenny, Darlynne; Tudorascu, Dana; Piro‐Gambetti, Brianna; Zammit, Matthew D.; Laymon, Charles M.; Klunk, William E.; Zaman, Shahid; Cohen, Annie; Christian, Bradley T.
Abstract: Introduction: There is a critical need to identify measures of cognitive functioning sensitive to early Alzheimer's disease (AD) pathophysiology in Down syndrome to advance clinical trial research in this at‐risk population. The objective of the study was to longitudinally track performance on cognitive measures in relation to neocortical and striatal amyloid beta (Aβ) in non‐demented Down syndrome. Methods: The study included 118 non‐demented adults with Down syndrome who participated in two to five points of data collection, spanning 1.5 to 8 years. Episodic memory, visual attention and executive functioning, and motor planning and coordination were assessed. Aβ was measured via [C‐11] Pittsburgh Compound‐B (PiB) PET. Results: PiB was associated with level and rate of decline in cognitive performance in episodic memory, visual attention, executive functioning, and visuospatial ability in models controlling for chronological age. Discussion: The Cued Recall Test emerged as a promising indicator of transition from preclinical to prodromal AD.